Differential Recruitment of Auditory Cortices in the Consolidation of Recent Auditory Fearful Memories - Cambiaghi, Marco (J Neurosci, 2016)
Memories of frightening events require a protracted consolidation process. Sensory cortex, such as the auditory cortex, is involved in the formation of fearful memories with a more complex sensory stimulus pattern. It remains controversial, however, whether the auditory cortex is also required for fearful memories related to simple sensory stimuli. In the present study, we found that, 1 d after training, the temporary inactivation of either the most anterior region of the auditory cortex, including the primary (Te1) cortex, or the most posterior region, which included the secondary (Te2) component, did not affect the retention of recent memories, which is consistent with the current literature. However, at this time point, the inactivation of the entire auditory cortices completely prevented the formation of new memories. Amnesia was site specific and was not due to auditory stimuli perception or processing and strictly related to the interference with memory consolidation processes. Strikingly, at a late time interval 4 d after training, blocking the posterior part (encompassing the Te2) alone impaired memory retention, whereas the inactivation of the anterior part (encompassing the Te1) left memory unaffected. Together, these data show that the auditory cortex is necessary for the consolidation of auditory fearful memories related to simple tones in rats. Moreover, these results suggest that, at early time intervals, memory information is processed in a distributed network composed of both the anterior and the posterior auditory cortical regions, whereas, at late time intervals, memory processing is concentrated in the most posterior part containing the Te2 region. SIGNIFICANCE STATEMENT Memories of threatening experiences undergo a prolonged process of “consolidation” to be maintained for a long time. The dynamic of fearful memory consolidation is poorly understood. Here, we show that 1 d after learning, memory is processed in a distributed network composed of both primary Te1 and secondary Te2 auditory cortices, whereas, at late time intervals, memory processing is concentrated in the most posterior Te2 cortex. Together, our data reveal that the consolidation of fearful memories related to simple auditory stimuli requires the auditory cortex, provided that the inactivation encompasses both the primary and the secondary components of the cortex, and that different regions of the auditory cortex play complementary but different roles in these processes.